Marketing Mix and Its Application in the Textile Sector in Ghana - Mohammed Majeed; Rebecca Lartekai Lartey; Joana Akweley Zanu (Fashion and Textiles Review, 2019)
The textile industry plays an essential role in most economies. For instance, the textile industry in Ghana used to be a large and thriving industry and contributed immensely to the nation’s employment generation, GDP, government revenues non-export earnings and constituted key exports to neighbouring African countries. However, in recent times the industry is faced with difficulties which have led to the closure of many firms in the industry, leading to the widespread unemployment with its associated issues. The study seeks to unveil the reasons behind this unfortunate development by determining the marketing tools used in by the firms and how they can apply the right marketing mix to increase their market share both internationally and locally. This study employed the descriptive survey design. The purposive sampling technique was used to select a sample size of eighty respondents from five local textile firms in the Tamale Municipality.